2012
DOI: 10.1097/icu.0b013e32835438fc
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma

Abstract: Purpose of review To review recent clinical and epidemiological studies regarding the prevention, diagnosis, and treatment of trachoma. Recent Findings Newer studies propose novel diagnostic tests that appear sensitive for the detection of ocular chlamydial infection. Immunologic studies suggest that chronic inflammation can lead to progressive scarring, even in the absence of chlamydia. Confocal microscopy can obtain accurate grading of scarring progression. Mass oral azithromycin distributions remain a mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 73 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…A review [126] of recent research in the prevention, diagnosis, and treatment of trachoma concluded that the SAFE strategy's mass treatment with antibiotics is the mainstay of trachoma treatment and is why community-targeted strategies are key to program success. Future research could focus on optimizing mass treatment by investigating integrated monitoring and treatment strategies at a community level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review [126] of recent research in the prevention, diagnosis, and treatment of trachoma concluded that the SAFE strategy's mass treatment with antibiotics is the mainstay of trachoma treatment and is why community-targeted strategies are key to program success. Future research could focus on optimizing mass treatment by investigating integrated monitoring and treatment strategies at a community level.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could focus on optimizing mass treatment by investigating integrated monitoring and treatment strategies at a community level. While the review covers a narrower timeframe and scope of literature, the most important conclusion reflects an overall finding of this current review—that trachoma elimination is possible even in hyperendemic communities [126]. …”
Section: Discussionmentioning
confidence: 99%
“…[420] With the implementation of SAFE strategy, trachoma has decreased in significance as a major cause of blindness. [212223] In 2002 and 2003, 84 million people across the world were suffering from active trachoma and ~1.3 million people were blind from trachoma. In 2002, ~3.6% of the total visual impairment was due to trachoma, which was the fourth major cause of blindness.…”
Section: Epidemiologymentioning
confidence: 99%
“…In 2002, ~3.6% of the total visual impairment was due to trachoma, which was the fourth major cause of blindness. [2122232425] In 2005, as per the WHO report, ~60 million people were suffering from trachoma and in 2008, 40 million people were suffering from active trachoma (WHO report, 2005 and 2008).…”
Section: Epidemiologymentioning
confidence: 99%
“…Acanthamoeba keratitis is less well understood, although there is an important role for Acanthamoeba lectins, proteases and possibly intracellular bacteria [10, 11]. As there are recent reviews on river blindness [4], trachoma [12], fungal keratitis [13] Acanthamoeba keratitis [10, 11] and HSV keratitis, the current review will focus on the mechanisms of innate immunity that underlie corneal inflammation and bacterial keratitis, primarily Pseudomonas aeruginosa keratitis. This review will also examine how P. aeruginosa virulence factors impair the host response and mediate bacterial replication in the cornea.…”
Section: Introductionmentioning
confidence: 99%